Geographic distribution: Liolaemus tirantii - Bulacios Arroyo, Ana Lucia (2019)
Departamento El Cuy: El Chocón (39.51250°S, 68.57583°W; WGS 84). 20 October2008. C. S. Abdala and G. J. Scrocchi. Verified by S. Quinteros. Museo Patagónico de Ciencias Naturales Juan Carlos Salgado, General Roca, Rio Negro, Argentina (MPCN-H 30). Cerro Policía, Puesto Yapeleo, 15 km N of Cerro Policía, El Barrial (39.64608°S, 68.78367°W; WGS 84), 474 m elev. 16 November 2015. C. S.Abdala, R. V. Semhan, M. M. Paz, and A. L. Bulacios Arroyo. Verified by S. Quinteros. Herpetological Collection Fundación Miguel Lillo, San Miguel de Tucumán, Tucumán, Argentina (FML 29722?29730). Specimens were active, sunning and feeding from 1000?1800 h in a region with greyish to brownish sandy soils.First province records, extending the known distribution 100 km SE from a previous record near pueblo La Amarga, Zapala Departament, Neuquén, Argentina (Avila et al. 2017. Zootaxa 4362:535?563). Project registered at Dirección de Fauna Silvestre de Río Negro (Exp. 085558-SAyDS-2015). The fieldwork wassupported by PICT 2263 and 1398, Agency for Scientific and Technological Promotion.